This distant and unsurveyed country : a woman's winter at Baffin Island, 1857-1858 - Ross, W. Gillies (William Gillies), 1931- (McGill-Queen's native and northern series, 1997)
Margaret Penny's journal with commentary and explanatory passages by Ross. W. Gillies.